Reference-less MR thermometry on pre-clinical thiel human cadaver for liver surgery with MRgFUS. - Karakitsios, Ioannis; Mihcin, Senay; Melzer, Andreas (Minimally Invasive Therapy & Allied Technologies)
Purpose: Reference-less MR thermometry can be a promising technique for temperature mapping during liver treatment with Magnetic Resonance-guided Focused Ultrasound (MRgFUS), as it is more robust to breathing motion than Proton Resonance Frequency MR thermometry. However, there is a lack of a pre-clinical model for repeatable testing of reference-less thermometry. The purpose of this work was to verify the explanted Thiel embalmed human liver and whole Thiel embalmed human cadaver for application of a custom made reference-less thermometry algorithm during MRgFUS sonication. Material and methods: Phase maps were generated during sonication as an input to the algorithm. A square Region-of-Interest (ROI) was designed around the heated area. The ROI was interpolated using a two-dimensional polynomial to the surrounding phase map to calculate the background phase. Results: Using the phase information from the images, the temperature rise was measured. Validation of the methodology showed accordance of temperatures with actual temperatures. Conclusions: The explanted liver and the whole cadaver constitute a promising and feasible model to study reference-less techniques for thermometry during MRgFUS, before clinical trials.